2014
DOI: 10.1097/mpg.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

Transient Neonatal Liver Disease After Maternal Antenatal Intravenous Ig Infusions in Gestational Alloimmune Liver Disease Associated With Neonatal Haemochromatosis

Abstract: Antenatal treatment with IVIG infusion in women at risk for gestational alloimmune disease recurrence improves the outcome of pregnancies despite mild signs of transient neonatal liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…So, in addition to the several possible mechanisms of action cited above for alloimmune thrombocytopenia, inhibition of activation of the terminal complement cascade may be important in the action of antenatal IVIG therapy in GALD. Whatever the mechanism, wide experience suggests that it is effective in limiting the effect of GALD in pregnancies at risk [11,15,[21][22][23][24][25][26][27]. Although the extent of protection from fetal liver injury in GALD cannot be ascertained to the same degree as in alloimmune thrombocytopenia, where the platelet count is a direct measure of effectiveness, the results in the present study clearly demonstrate improved outcomes with IVIG treatment.…”
Section: Discussionmentioning
confidence: 54%
“…So, in addition to the several possible mechanisms of action cited above for alloimmune thrombocytopenia, inhibition of activation of the terminal complement cascade may be important in the action of antenatal IVIG therapy in GALD. Whatever the mechanism, wide experience suggests that it is effective in limiting the effect of GALD in pregnancies at risk [11,15,[21][22][23][24][25][26][27]. Although the extent of protection from fetal liver injury in GALD cannot be ascertained to the same degree as in alloimmune thrombocytopenia, where the platelet count is a direct measure of effectiveness, the results in the present study clearly demonstrate improved outcomes with IVIG treatment.…”
Section: Discussionmentioning
confidence: 54%
“…As such, preventing the recurrence of NH is very important. It has been reported that high‐dose Ig for recurrent NH is safe and effective, but the present case has highlighted two issues regarding this treatment that had been unclear.…”
Section: Discussionmentioning
confidence: 81%
“…Neonatal hemochromatosis is a clinical syndrome in which liver disease in the newborn is accompanied by siderosis of hepatic and extrahepatic tissues in the pattern seen in hereditary hemochromatosis. 1,5,8 Studies suggested a genetic prevalence of 0.03-0.038 or a heterozygosity prevalence of 6-7%. 10 Gestational alloimmune liver disease is a materno-fetal alloimmune disorder directed at the fetal liver, often producing neonatal liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…
Neonatal hemochromatosis (NH) is a rare fatal liver disease accompanied by hepatic and extrahepatic iron overload. [1][2][3] Gestational alloimmune liver disease (GALD) is a materno-fetal alloimmune disorder and leading cause of NH. 2,4,5 This condition allows an interplay between the maternal adaptive immune system and the fetus, resulting in an allograft to the mother.
…”
mentioning
confidence: 99%